Cellulase Linkers Are Optimized Based on Domain Type and Function: Insights from Sequence Analysis, Biophysical Measurements, and Molecular Simulation - Sammond, Deanne W.; Payne, Christina M.; Brunecky, Roman; Himmel, Michael E.; Crowley, Michael F.; Beckham, Gregg T. (PLOS ONE, 2012)
Cellulase enzymes deconstruct cellulose to glucose, and are often comprised of glycosylated linkers connecting glycoside hydrolases (GHs) to carbohydrate-binding modules (CBMs). Although linker modifications can alter cellulase activity, the functional role of linkers beyond domain connectivity remains unknown. Here we investigate cellulase linkers connecting GH Family 6 or 7 catalytic domains to Family 1 or 2 CBMs, from both bacterial and eukaryotic cellulases to identify conserved characteristics potentially related to function. Sequence analysis suggests that the linker lengths between structured domains are optimized based on the GH domain and CBM type, such that linker length may be important for activity. Longer linkers are observed in eukaryotic GH Family 6 cellulases compared to GH Family 7 cellulases. Bacterial GH Family 6 cellulases are found with structured domains in either N to C terminal order, and similar linker lengths suggest there is no effect of domain order on length. O-glycosylation is uniformly distributed across linkers, suggesting that glycans are required along entire linker lengths for proteolysis protection and, as suggested by simulation, for extension. Sequence comparisons show that proline content for bacterial linkers is more than double that observed in eukaryotic linkers, but with fewer putative O-glycan sites, suggesting alternative methods for extension. Conversely, near linker termini where linkers connect to structured domains, O-glycosylation sites are observed less frequently, whereas glycines are more prevalent, suggesting the need for flexibility to achieve proper domain orientations. Putative N-glycosylation sites are quite rare in cellulase linkers, while an N-P motif, which strongly disfavors the attachment of N-glycans, is commonly observed. These results suggest that linkers exhibit features that are likely tailored for optimal function, despite possessing low sequence identity. This study suggests that cellulase linkers may exhibit function in enzyme action, and highlights the need for additional studies to elucidate cellulase linker functions.